Campus education and information and communication technologies: obstacles and possibilities in times of pandemic (International Seven Journal of Multidisciplinary, 2023)
This work, whose theme is Rural Education and Information and Communication Technologies: Obstacles and possibilities in times of Pandemic, presents reflections on the challenges and strategies adopted to guarantee the access and permanence of peasant students to the EMEIF Odil Pontes school during the social distancing resulting from the COVID-19 pandemic, where face-to-face teaching was replaced by remote teaching and the teacher began to develop a strategy using technology to continue the school period, enabling a teaching and learning process that encompassed all students. The teaching practice has become a challenge both for the school and especially for the teachers who should improve teaching aiming at methodologies that include technological devices in order to enable the continuity of teaching and learning. It is intended to discuss the possibilities and obstacles that public education systems in the municipality of Tome-Açu faced to continue school activities during the period of social distancing in 2020. To better address the issue, a qualitative research is developed through a case study in which the data collection instrument was carried out through a structured questionnaire with open questions in order to verify the current problem caused by COVID-19, considering the social and educational aspects. The research is concluded, based on the discussion of the results by analyzing the content of the participants' speeches, which brought a detailed view of the problems and obstacles that the pandemic caused in the researched location.